Специфіка податкового планування: вітчизняні реалії та зарубіжний досвід - Піхур, Андрій Романович; Pihur, Andriy Romanovych (Ірпінь, 2023)
На основі узагальнення розглянуто дослідження теоретико-методичних та організаційно-правових особливостей податкового планування транснаціональних корпорацій та промислово-фінансових груп в Україні та світі. За результатами дослідження обґрунтовані теоретичні напрями удосконалення податкового планування фінансово-промислових груп та транснаціональних господарських структур в умовах виконання Україною правил BEPS, які можуть бути використані у проведенні наукових досліджень з цієї тематики.

Based on the generalization, the study of theoretical-methodical and organizational-legal features of tax planning of transnational corporations and industrial-financial groups in Ukraine and the world is considered. Based on the results of the study, the theoretical directions for improving the tax planning of financial and industrial groups and transnational economic structures in the conditions of Ukraine's implementation of the BEPS rules, which can be used in conducting scientific research on this topic, are substantiated.
Specifics of tax planning: domestic realities and foreign experience
Keywords: податкове планування; промислово-фінансові групи; транснаціональні корпорації; офшори; tax planning; industrial and financial groups; transnational corporations; offshore companies